Cytidine-containing tails robustly enhance and prolong protein production of synthetic mRNA in cell and in vivo - Cheuk Yin Li; Zhenghua Liang; Yaxin Hu; Hongxia Zhang; Kharis Daniel Setiasabda; Jiawei Li; Shaohua Ma; Xiaojun Xia; Yi Kuang (Elsevier, 2022)
Synthetic mRNAs are rising rapidly as alternative therapeutic agents for delivery of proteins. However, the practical use of synthetic mRNAs has been restricted by their low cellular stability as well as poor protein production efficiency. The key roles of poly(A) tail on mRNA biology inspire us to explore the optimization of tail sequence to overcome the aforementioned limitations. Here, the systematic substitution of non-A nucleotides in the tails revealed that cytidine-containing tails can substantially enhance the protein production rate and duration of synthetic mRNAs both in vitro and in vivo. Such C-containing tails shield synthetic mRNAs from deadenylase CCR4-NOT transcription complex, as the catalytic CNOT proteins, especially CNOT6L and CNOT7, have lower efficiency in trimming of cytidine. Consistently, these enhancement effects of C-containing tails were observed on all synthetic mRNAs tested and were independent of transfection reagents and cell types. As the C-containing tails can be used along with other mRNA enhancement technologies to synergically boost protein production, we believe that these tails can be broadly used on synthetic mRNAs to directly promote their clinical applications.